Cultural Imprinting and Leadership in Higher Education: A Systematic Literature Review from the Perspective of Emerging Countries - Natalina Damayanthi (Universitas Pelita Harapan, 2026)
This study examines how cultural imprinting, values internalized during early socialization, shapes leadership orientations and strategic leadership practices in higher education, particularly in emerging-country contexts. A systematic literature review (SLR) of peer-reviewed studies published between 2020 and 2025 was conducted following PRISMA guidelines to synthesize leadership, cross-cultural, and imprinting scholarship. The review identifies three thematic domains: (1) cultural imprinting and leadership orientation, (2) contextual variations between Western and emerging-country leadership practices, and (3) strategic implications for internationalization, digital transformation, and graduate reputation. Building on these insights, this study proposes an integrative conceptual framework, the Cultural Imprinting Leadership Framework, synthesizing imprinting theory, cross-cultural leadership perspectives, and strategic leadership in higher education. The study contributes theoretically by extending leadership theory through the integration of cultural imprinting, contextually by highlighting leadership dynamics in emerging countries, and practically by informing culturally grounded leadership development strategies. However, the findings are conceptual and require empirical validation through future cross-cultural and longitudinal research.